2020
DOI: 10.1007/s11119-020-09766-8
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for precise lime management based on high-resolution soil pH, texture and SOM maps generated from proximal soil sensing data

Abstract: Soil acidification is caused by natural paedogenetic processes and anthropogenic impacts but can be counteracted by regular lime application. Although sensors and applicators for variable-rate liming (VRL) exist, there are no established strategies for using these tools or helping to implement VRL in practice. Therefore, this study aimed to provide guidelines for site-specific liming based on proximal soil sensing. First, high-resolution soil maps of the liming-relevant indicators (pH, soil texture and soil or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Finally, they produced 2 × 2 m maps of the actual soil acidity (pH), SOM and soil texture (clay, silt, and sand). Bönecke et al [17] used these generated soil maps and the stepless algorithm to successfully produce variable rate lime application maps. They compared the variable liming rates with a standard uniform liming approach and found that 63% of the field would be over-fertilized by approximately 12 Mg of lime, 6% would receive approximately 6 Mg too little lime and 31% would still be adequately limed under the uniform liming approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, they produced 2 × 2 m maps of the actual soil acidity (pH), SOM and soil texture (clay, silt, and sand). Bönecke et al [17] used these generated soil maps and the stepless algorithm to successfully produce variable rate lime application maps. They compared the variable liming rates with a standard uniform liming approach and found that 63% of the field would be over-fertilized by approximately 12 Mg of lime, 6% would receive approximately 6 Mg too little lime and 31% would still be adequately limed under the uniform liming approach.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers can use these tables without calculations and without special expert knowledge to assess the lime demand for their fields. Over the last 40 years, the VDLUFA look-up table system has served the agricultural needs of lime fertilization very well but has to be considered very rough, especially in relation to new results of soil texture mapping [17][18][19]. As was shown in these studies, soil data can now be determined very accurately and with a high degree of spatial accuracy using on-the-go soil sensors and digital soil mapping techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The soil sampling sites for BNC laboratory analysis were taken in accordance with the procedure proposed by Bönecke et al (2020), considering that the targeted samples: (i) cover A total of 164 soil samples (Fig. 1) were analyzed for base neutralizing capacity (BNC).…”
Section: Lr Based On Base Neutralizing Capacity (Lr Bnc )mentioning
confidence: 99%
“…Von Cossel et al (2019) deployed low-input sensor-based soil mapping of electromagnetic induction (EMI) (EM38 MK I; Geonics, Canada) in combination with in situ and ex situ pH measurements to determine the soil's LR. Bönecke et al (2020) applied an on-the-go multi-sensor approach using the Veris Mobile Sensor Platform and the Geophilus Electricus (Geophilus GmbH, Germany) proximal soil sensing system (Lück and Rühlmann, 2013). By combining the sensor data with reference analyses of soil characteristics that are well-correlated with soil acidity and soil pH buffer capacity, high-resolution soil maps of pH, texture and soil organic matter (SOM) were generated.…”
Section: Introductionmentioning
confidence: 99%
“…Considering variations in soil texture within a field is now possible with global positioning system (GPS) and precision agriculture (PA). The aim of these technologies is to divide the field into homogenous management zones suitable for optimal site-specific management of fertilization [6], liming [7], and drainage and irrigation [8]. Consequently, recommending the same management practices irrespective to the textural group can lead to unwanted high crop yield variability.…”
Section: Introductionmentioning
confidence: 99%